Les Images Contrastées Des Femmes Émergentes De La Société Civile Et Transformation Des Rôles Sociaux Sexués En Province Orientale Post-Mobutu - Omeyaka, Bibiche Liliane Salumu Laumu (European Scientific Journal, ESJ, 2017)
This article approaches the subversive dimension and performative gender in women awakeness in Oriental Province post-Mobutu era. Their ambition wobbles between maintaining feminine leadership status (their high-flying female) which takes its subsistence from the implementation of their capability and their sufferance from social representation in an environment dominated by patriarchal stereotypes and a political system less disposed to take actions in gender matters. However, feminine elite’s capability procreates social transformations across a social deconstruction not only in role of sexes in the society (structural transformations) but also in transformations observed in man to woman and woman to woman relationship. Under this optics, these civil society women really become actors of change in women well-being in their area. Their way of thinking, acting and being make them convinced feminists. But, the opposite is also possible when some of them resign themselves to break the wall of glass sheltering inequalities between sexes for other aims, notably political. They are selective in their involvement. In that case, they are common feminists of use, most often, as footbridge for politicians. It is on base of the analysis model socio dynamic model analysis which we had achieved in better reconciling structural complexity of those social representations and their insertion in plural social and ideological contexts in Oriental province after President Mobutu reign.